2018
DOI: 10.1371/journal.pone.0194974
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic examination of keel bone damage in living laying hens of different strains kept in two housing systems

Abstract: A high prevalence of deviations and fractures of the keel bone is a widespread welfare problem in laying hens. The aim of this study was to experimentally investigate this multifactorial problem throughout the laying period and to compare the prevalence and severity in different layer lines and different housing systems. High performing white (WLA) and brown (BLA) pure bred layer lines and low performing white (R11, G11) and brown layer lines (L68) were kept in both single cages and a floor housing system. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
85
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(98 citation statements)
references
References 35 publications
11
85
0
2
Order By: Relevance
“…They found a lower number of experimental fractures in the experimental line (24). Similarly, we found a higher prevalence of keel bone fractures and more severe keel bone deviations in a high compared to a low performing brown layer line in a previous study (19). However, in the same study, no such clear differences between high and low performing layer lines were found within the white layers (19).…”
Section: Introductionsupporting
confidence: 71%
See 4 more Smart Citations
“…They found a lower number of experimental fractures in the experimental line (24). Similarly, we found a higher prevalence of keel bone fractures and more severe keel bone deviations in a high compared to a low performing brown layer line in a previous study (19). However, in the same study, no such clear differences between high and low performing layer lines were found within the white layers (19).…”
Section: Introductionsupporting
confidence: 71%
“…Digital radiographs were taken and evaluated as previously described (19). The non-anesthetized hen was gently placed on its left side on the digital flat panel detector Thales Pixium 2430 EZ wireless (Thales Electron Devices S.A., Vélizy-Villacoublay, France) and lateral radiographs were taken with 50.0 kV and at 2 mAs using the X-ray apparatus WDT Blueline 1040 HF (Wirtschaftsgenossenschaft deutscher Tierärzte eG, Garbsen, Germany) and the X-ray suitcase Leonardo DR mini (Oehm und Rehbein GmbH, Rostock, Germany).…”
Section: Radiographic Examination Of the Keel Bonementioning
confidence: 99%
See 3 more Smart Citations